Pemenuhan Hak Konstitusi Atas Pendidikan Dalam Perspektif Siyasah Dusturiyyah: Studi Kasus Pasal 31 Ayat 1 UUD 1945 - Elzian Syahputra, Muhammad Akbar; Suganda, Delfi; Fithria, Nurul (IAI Darussalam, 2026)
This study examines the constitutional guarantee of the right to education under Article 31 of the 1945 Constitution of Indonesia through the integrative lens of Islamic constitutional theory (siyasah dusturiyyah). Using a normative-descriptive method, this research analyzes primary legal sources, classical Islamic texts, and empirical data to investigate the implementation gaps in educational rights. The findings reveal significant disparities between constitutional mandates and empirical realities, with 8.5% of school-age children lacking access to formal education and extreme regional inequalities in educational participation. From the siyasah dusturiyyah perspective, the state bears dual responsibility: legal under the constitution and moral-spiritual under Islamic principles of leadership (imamah) and the protection of intellect (hifzh al-'aql). The study develops three integrative models complementary, convergent, and transformative to address structural educational inequalities. These findings emphasize that integrating constitutional and Islamic legal approaches provides a holistic framework for developing more equitable and inclusive education policies in Indonesia's multicultural context. The research recommends budgetary reorientation towards underdeveloped regions, affirmative action based on integrative justice principles, and enhanced monitoring systems combining public accountability and Islamic oversight principles (hisbah).